Automated Cloud Based Long Short-Term Memory Neural Network Based SWE Prediction - Meyal, Alireza Yekta; Versteeg, Roelof; Alper, Erek; Johnson, Doug; Rodzianko, Anastasia; Franklin, Maya; Wainwright, Haruko (Frontiers in Water, 2020)
Snow derived water is a critical component of a large part of the US water supply. Measurements of the Snow Water Equivalent (SWE) and associated predictions of peak SWE and snowmelt onset are essential inputs for water management efforts. This paper aims to develop a data-driven approach for estimating and predicting SWE dynamics using the Long Short-Term Memory neural network (LSTM) method. Our approach uses historical datasets (precipitation, air temperature, SWE and snow thickness) collected at NRCS Snow Telemetry (SNOTEL) stations to train the LSTM network and current year data to predict SWE behavior. The performance of our prediction was compared for different prediction dates and prediction training datasets. Our results suggest that the proposed LSTM network can be an efficient tool for forecasting the SWE timeseries, as well as Peak SWE and snowmelt timing. Results showed that the window size impacts the model performance (where the Nash Sutcliffe efficiency (NSE) ranged from 0.96 to 0.85 and the Rooted Mean Square Error (RMSE) ranged from 0.038 to 0.07) with an optimum number that should be calibrated for different stations and climate conditions. By implementing the LSTM prediction capability in a cloud based site-monitoring platform we automate model-data integration. By making the data accessible through a graphical web interface and an underlying API which exposes both training and prediction capabilities. the associated results can be made easily accessible to a broad range of stakeholders.